Pengaruh Profitabilitas Dan Pertumbuhan Perusahaan Terhadap Inilai Perusahaan Pada Perusahaan Pt H.M Sampoerna Yang Terdaftar Di Bursa Efek Indonesia I Periode 2016-2020 - Ivana Elisabet Siahaan; Teddi Pribadi; Muhamad Yamin Siregar; Hesti Sabrina; Alfifto Alfifto (Universitas Medan Area, 2023)
This study aims to examine and find out how the effect of Profitability (ROE) and Company Growth (TAG) on Firm Value (PBV) at PT H.M Sampoerna which is listed on the Indonesia Stock Exchange. This research is an associative research and the type of data used is quantitative data. The first data analysis technique is descriptive statistics, classical assumption test, multiple linear regression analysis, then hypothesis testing with the help of SPSS 25 application. The results of this study indicate that partially profitability has a positive and significant effect on firm value and firm growth has a positive and significant effect on firm value. Simultaneously it was found that profitability and company growth had a positive and significant effect on firm value.